An Integrative Assessment Combining Deep-Sea Net Sampling, in situ Observations and Environmental DNA Analysis Identifies Cabo Verde as a Cephalopod Biodiversity Hotspot in the Atlantic Ocean - Merten, Véronique; Bayer, Till; Reusch, Thorsten B. H.; Puebla, Oscar; Fuss, Janina; Stefanschitz, Julia; Lischka, Alexandra; Hauss, Helena; Neitzel, Philipp; Piatkowski, Uwe; Czudaj, Stephanie; Christiansen, Bernd; et al. (Frontiers in Marine Science, 2021)
The deep sea is among the largest, most biologically diverse, yet least-explored ecosystems on Earth. Baseline information on deep-sea biodiversity is crucial for understanding ecosystem functioning and for detecting community changes. Here, we established a baseline of cephalopod community composition and distribution off Cabo Verde, an archipelago in the eastern tropical Atlantic. This baseline served to test the hypothesis that Cabo Verde is biogeographically separated from other Macaronesian archipelagos and allowed the identification of cephalopod species which may play a role in the Macaronesian carbon cycle and oceanic food web. To investigate cephalopod community composition, this study used 746 individual cephalopods obtained by nets (0–1000 m) and 52 cephalopod encounters during video surveys with either towed camera (0–2500 m) or manned submersible (0–375 m). Additionally, environmental DNA (eDNA) metabarcoding on 105 seawater samples (50–2500 m), using an 18S rRNA universal cephalopod primer pair, and a species-specific primer pair for Taningia danae resulted in the detection of 32 cephalopod taxa. When combined, the three methods detected a total of 87 taxa, including 47 distinct species. Each method contributed between 7 and 54% of taxa that were not detected by the other methods, indicating that multiple methodological approaches are needed for optimal deep-sea cephalopod biodiversity assessments. This study documents the occurrences of six species and three genera for the first time in waters surrounding Cabo Verde. Video surveys and eDNA analysis detected Taningia danae recurrently (100–2500 m). eDNA metabarcoding proved to be a powerful tool for cephalopod biodiversity monitoring and complementary to traditional sampling methods. When also including literature records, Cabo Verde hosts at least 102 cephalopod taxa including 30 families and 64 benthic and pelagic species. The total number and species composition of Cabo Verde cephalopods is similar to the Canary Islands and Azores, two known cephalopod biodiversity hotspots, but the Cabo Verde octopus fauna seems to differ. Due to a range of life history characteristics, we hypothesize that the squids Taningia danae (Octopoteuthidae) and Sthenoteuthis pteropus (Ommastrephidae) are important in the carbon cycle of Macaronesia. As a cephalopod biodiversity hotspot Cabo Verde could function as a model region to investigate cephalopod biology and ecology in a rapidly changing Atlantic Ocean.